factors related to the event of gastritis disease in kelurahan tanjung pinang, jambi city in 2018 - yenni, melda; sugiarto, sugiarto; rumiati, rumiati (Jurnal Formil (Forum Ilmiah) Kesmas Respati, 2019)
Non-communicable diseases are a major health problem in developing countries that are experiencing a demographic transition and a decline in lifestyle in their communities. The WHO 2013 World Health Research Agency, conducted a review of several countries in the world, obtained a percentage of gastritis in the world, including Britain 22%, China 31%, Japan 14.5%, Canada 35%, and France 29.5%. Based on data from the Jambi City Health Office from 20 puskesmas the number of gastritis cases was 83.21% and the highest number of gastritis events was at tanjung pinang health center, which was 5.91%. This study was conducted to determine the factors associated with the incidence of gastritis in Tanjung Pinang Village, Jambi City. The research design used was quantitative with a cross sectional approach. The population in this study was the productive age community in the area of Tanjung Pinang which numbered 9,489 people. The sampling technique uses Random Sampling techniques with a total sample of 95 respondents. This research was conducted on September 28, October 16, 2018. Data obtained were analyzed by univariate and bivariate using the Chi-Square test. The results showed that there was a relationship between eating patterns with the incidence of gastritis p-value 0,000 (P-Value <0.05), coffee consumption with the incidence of gastritis p-value 0.027 (P-Value <0.05) and the relationship of stress levels with Gastritis incidence p-value 0,000 (P-Value <0.05). It is expected that respondents and the community will always maintain a regular diet, reduce or limit coffee consumption in a day, and exercise for one hour and relax regularly, recreation/refreshing, share or manage work time properly